The Relation of Religion and Culture in the Review of Indonesian Islamic Community Development - Rahmah Dwi Nopryana; Indah Susilowati (International Journal on Advanced Science, Education, and Religion, 2022)
The article aims to find out the relationship between religion and culture according to religious and cultural texts that apply in the context of developing Indonesian Islamic society. The reserchers used descriptive qualitative research method and collect data from several related sources. The result show that the relationship between religion and culture has been going on for a long time in Indonesia, where this religion develops and is influenced by local culture and that culture is carried out by being escorted by religion to be in line with religious goals. Islam influences the development of Indonesian society by bringing their culture in line with the Shari'a so that they become shalah 'inda Allah and shalah 'inda nas. This is part of the peak of civilization for the Indonesian Muslim community. Religion recognizes and gives legality to culture that is in line with religious goals and does not oppose religious texts. However, what is still lacking is how the culture is created so that it is in harmony with religion Keywords: Religion and Culture, Relation Religcion and Culture, Islamic Community Development